A SNAP-25 cleaving chimera of botulinum neurotoxin /A and /E prevents TNFα−induced elevation of the activities of native TRP channels on early postnatal rat dorsal root ganglion neurons. (August 2018) - Nugent, Marc; Yusef, Yamil R.; Meng, Jianghui; Wang, Jiafu; Dolly, J. Oliver
Abstract: Transient receptor potential (TRP) vallinoid 1 (TRPV1) and ankyrin 1 (TRPA1) are two transducing channels expressed on peripheral sensory nerves involved in pain sensation. Upregulation of their expression, stimulated by inflammatory cytokines and growth factors in animal pain models, correlate with the induction of nociceptive hyper-sensitivity. Herein, we firstly demonstrate by immuno-cytochemical labelling that TNFα augments the surface content of these channels on rat cultured dorsal root ganglion (DRG) neurons which, in turn, enhances the electrophysiological and functional responses of the latter to their specific agonists. A molecular basis underlying this TNFα-dependent enhancement was unveiled by pre-treating DRGs with a recently-published chimeric protein, consisting of the protease light chain (LC) of botulinum neurotoxin (BoNT) serotype E fused to full-length BoNT/A (LC/E-BoNT/A). This cleaves s yn aptosomal-a ssociated p rotein of Mr 25 k (SNAP-25) and reported previously to exhibit anti-nociceptive activity in a rat model of neuropathic pain. Low pM concentrations of this chimera were found to prevent the TNFα-stimulated delivery of TRPV1/A1 to the neuronal plasmalemma and, accordingly, decreased their incremental functional activities relative to those of control cells, an effect accompanied by SNAP-25 cleavage. Advantageously, LC/E-BoNT/A did not reduce the basal surface contents of the two channels or their pharmacological responses. Thus, use of multiple complementary methodologies provides evidence that LC/E-BoNT/A abolishes the TNFα-dependent augmented, but not resting, surface trafficking of TRPV1/A1. As TNFα is known to induce nociceptive hyper-sensitivity in vivo, our observed inhibition by LC/E-BoNT/A of its action in vitro could contribute to its potential alleviation of pain. Highlights: TNFα increases the surface content of TRPV1/A1 channels in DRG neurons. Consequently, the latter have enhanced functional activities in response to specific agonists. These incremental effects are prevented by a chimera of botulinum neurotoxin A-E. TNFα-dependent escalations, but not resting levels, are inhibited by pM amounts of this chimera.